Compétence, compétences transversales et compétences clés : peut-on sortir de l’impasse ? - Jean-Claude Coulet (Éducation et Socialisation)
The concept of competence has become essential, both within organisations and in the field of education and training. However it remains difficult, especially for professionals, not to get lost in the terminological and conceptual jungle of the vast literature devoted to it. This article proposes a critical analysis of this literature and discusses, in particular, the place and the status given to "transversal competences" and "key competences". Furthermore, with a reference to theories of activity, it presents two theoretical models, inducing some ways in order to break the deadlock in which we are engaged today.